Description of Physical Activity and Sedentary Lifestyle in Employees of the Medical Faculty of Swadaya Gunung Jati University - Kati Siwiyati; Coryna Frisqila; Novi Robbayanti; Salasabila Carissa, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Low physical activity and sedentary lifestyle are among the risk factors for various non-communicable diseases, such as obesity, diabetes, and cardiovascular disease. Employees as a group who spend most of their time at work are at high risk of sedentary lifestyle. Therefore, it is important to know the description of physical activity and the level of sedentary lifestyle in employees in the college environment. This study aims to determine the description of physical activity and sedentary lifestyle in employees of Swadaya Gunung Jati University. The type of research used is descriptive analytic with a sample size of 78 employees. Data processing was carried out by analytical method using the Global Physical Activity Questionnaire (GPAQ) instrument to measure the intensity and duration of physical activity and sedentary lifestyle patterns. The results showed that 20.51% of employees had heavy physical activity with an average duration of 16 minutes per day, 61.54% of employees did moderate physical activity with an average duration of 55 minutes per day, 65.38% of employees walked or cycled when going to work with an average activity duration of 27 minutes per day. A total of 28.21% of employees do vigorous exercise with an average duration of 20 minutes per day, and 57.69% of employees do moderate exercise with an average duration of 37 minutes per day. The average employee does not do much physical activity with a total duration of 120 minutes per day, indicating a tendency towards a sedentary lifestyle. This study shows that most employees of Universitas Swadaya Gunung Jati have moderate physical activity, but there are still sedentary lifestyle tendencies in this group. These findings emphasize the importance of efforts to increase physical activity and interventions to reduce sedentary lifestyle among employees.